The Influence of Barbershop Interior Design Elements on Visitor Comfort (Case Study at Chaptain Barbershop) - Muhammad Akira; Muhajirin Muhajirin; Feni Aryani (Journal of Economics, Management and Accounting (JEMA), 2025)
This study aims to analyze the influence of interior design elements on visitor comfort at Chaptain Barbershop. The design elements examined include lighting, color, spatial layout, air circulation, and furniture. The research employed a quantitative approach using a questionnaire distributed to 100 respondents who are customers of Chaptain Barbershop. The collected data were analyzed using validity and reliability tests, multiple linear regression, as well as F-test and t-test to examine the hypotheses. The results indicate that lighting, spatial layout, and furniture have a significant effect on visitor comfort, while color and air circulation also have an impact but are less dominant. Simultaneously, all five interior design elements positively contribute to visitor comfort. These findings highlight the importance of proper interior design arrangements in enhancing the quality of customer experience in service spaces.